2016
DOI: 10.1093/nar/gkw878
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cGAS-dependent antiviral responses by DNA intercalating agents

Abstract: Acridine dyes, including proflavine and acriflavine, were commonly used as antiseptics before the advent of penicillins in the mid-1940s. While their mode of action on pathogens was originally attributed to their DNA intercalating activity, work in the early 1970s suggested involvement of the host immune responses, characterized by induction of interferon (IFN)-like activities through an unknown mechanism. We demonstrate here that sub-toxic concentrations of a mixture of acriflavine and proflavine instigate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 41 publications
4
38
0
Order By: Relevance
“…It was first identified as a conserved enzyme that synthesizes cyclic dinucleotides. Previous studies have shown that cGAS is mainly located in the cytoplasm, and its expression is induced by cytoplasmic dsDNA molecules (27). In this study, we found that cGAS protein tended to decline from 0 to 6 h after treatment with mtDNA.…”
Section: Discussionsupporting
confidence: 55%
“…It was first identified as a conserved enzyme that synthesizes cyclic dinucleotides. Previous studies have shown that cGAS is mainly located in the cytoplasm, and its expression is induced by cytoplasmic dsDNA molecules (27). In this study, we found that cGAS protein tended to decline from 0 to 6 h after treatment with mtDNA.…”
Section: Discussionsupporting
confidence: 55%
“…Notably, cGAS also regulates immune responses in the absence of infection through the detection of endogenous (self) DNA. For instance, cGAS promotes IFN responses to genotoxic stress induced by DNA damaging agents, micronuclei formation, and cellular senescence (Dou et al, 2017;Glü ck et al, 2017;Harding et al, 2017;Hä rtlova et al, 2017;Mackenzie et al, 2017;Pé pin et al, 2017;Yang et al, 2017). cGAS is therefore not only a sensor of pathogens but also a sensor of cellular stress and genomic integrity.…”
Section: Introductionmentioning
confidence: 99%
“…PRO seems to alter the microenvironment of tryptophan residues compared with tyrosine residues [60]. Another effect of PRO observed at the nuclear level is represented by its antitumoral effect [31] with only minimal damage to DNA, which is then potentiated by immune recruitment and, as a non-covalent binder to DNA, it can act as an indirect cyclic GMP-AMP Synthase cGAS agonist [62].…”
Section: Proflavinementioning
confidence: 99%
“…The response obtained when sub-toxic doses of PRO were used, was directly dependent on cell type, since cytoplasmatic DNA leakage was absent in L929 murine cell, which express functional levels of cGAS and STING. However, the DNA damage was still present [62].…”
Section: Proflavine Uses For In Vitro Studiesmentioning
confidence: 99%